(Przed)wczesne macierzyństwo - perspektywa biograficzna. Diagnoza, pomoc i wsparcie - Skowrońska-Pućka, Agnieszka (Wydawnictwo Naukowe UAM, 2016)
The Polish literature still doesn’t refer to the social problem of premature maternity, when a girl becomes pregnant or has a baby before she comes of age. This topic is discussed much more frequently among doctors and sociologists than teachers. Researchers concentrate more on the psychological and social consequences than on the pedagogical perspective of the subject. At the same time, there are children having children in our country every year. Experts on the problem say the statistics do not take the entire phenomenon into account; however, there is still reason to be concerned. The demographical yearbook of the Central Statistical Office of Poland indicates that 16,000 teenagers gave birth in 2011. The subject of my research was young girls’ experience of premature pregnancy and the responsibilities resulting from premature motherhood. I wanted to know what they feel, and to help and support them, which is why I tried to describe their situation and their prospects for the future. The research is focused on three main issues: the crisis of a complicated biographical situation: both being prematurely pregnant and put in an educational care facility; having a new role – performing the duties of a mother, being a mother and a student, as well as other social roles typical for an adolescent; the reactions of the closest group of people; assessment of the educational care facility’s role and other institutional and non-institutional forms of support for young mothers, along with the mothers’ demands and expectations of social support. I sought answers to my theses using qualitative research methods (biographical method). I chose this kind of empirical verification because it allows subjective phenomena to be shown and through meetings with the teenage mothers who are the subject of my research, it is possible to find out about their experiences and lifestyle.

Przedmiotem badań prezentowanej monografii jest świat młodych dziewcząt, wychowanek placówek opiekuńczo-wychowawczych, doświadczonych (przed)wczesną ciążą i wynikającym z niej (przed)wczesnym obowiązkiem macierzyńskim. W polskiej literaturze dotyczącej nauk społecznych problem (przed)wczesnego macierzyństwa należy do zagadnień mało znanych i rzadko opisywanych, zdecydowanie częściej jest on tematem prac lekarzy. Tymczasem każdego roku w naszym kraju przychodzą na świat dzieci powite przez matki, które same są jeszcze dziećmi. Jak zauważają znawcy problematyki, statystyki w Polsce nie uwzględniają całości zjawiska, a dostępne dane budzą niepokój: rocznik demograficzny Głównego Urzędu Statystycznego wskazuje na ponad szesnaście tysięcy urodzeń przez nastolatki w 2011 roku. W prezentowanych badaniach skoncentrowano się wokół następujących zagadnień: kryzysu podwójnego uwikłania biograficznego spowodowanego przedwczesną ciążą i jednoczesnym umieszczeniem w placówce opiekuńczo-wychowawczej; funkcjonowania w nowej roli (pełnienia obowiązków macierzyńskich, godzenia roli matki z rolą uczennicy i innymi charakterystycznymi dla adolescenta rolami społecznymi); reakcji najbliższego otoczenia; oceny przez małoletnie matki roli placówki opiekuńczo-wychowawczej i innych instytucjonalnych czy pozainstytucjonalnych form wsparcia, w tym ich postulatów i oczekiwań w zakresie wsparcia społecznego. Aby uzyskać odpowiedzi na postawione pytania, w pracy zastosowano jakościowy sposób prowadzenia badań, wykorzystując metodę biograficzną. Taka weryfikacja empirycznych danych pozwala ukazać subiektywne, niemierzalne zjawiska, a dzięki autentycznemu spotkaniu badacza z badanym możliwe staje się poznanie doświadczeń konkretnych osób – w omawianym przypadku małoletnich matek – w ich środowisku życia.
Keywords: małoletnie matki; ciąża; macierzyństwo; piecza zastępcza; placówka opiekuńczo-wychowawcza; adolescencja; wydarzenie krytyczne; wsparcie społeczne